The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1007/s11010-010-0637-9
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome proliferator-activated receptor γ agonist pioglitazone inhibits β-catenin-mediated glioma cell growth and invasion

Abstract: Gliomas are the most common primary tumors of the central nervous system. Rapid proliferation and diffuse brain invasion of these tumors are likely to determine the unfavorable prognosis. Recent studies have shown that ligand activation of peroxisome proliferator-activated receptor γ (PPARγ) can induce differentiation and inhibit proliferation of several cancer cells. In this study, we identified pioglitazone, one PPARγ ligand in particular, suppressed human glioma cells proliferation, migration, and induced g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 32 publications
1
39
1
Order By: Relevance
“…These have been found in all the mammalian species that have been examined to date (9,10). PPAR-␥ is highly expressed in cancer cells, and treatment with PPAR-␥ ligands can induce cell differentiation and apoptosis (11)(12)(13). Existing endogenous ligands for PPAR-␥ include polyunsaturated fatty acids and the eicosanoids 15-deoxy-⌬12,14-prostaglandin J2 (15d-PGJ2), 13-hydroxyoctadecadienoic acid, and 15-hydroxyeicosatetraenoic acid (14,15).…”
mentioning
confidence: 99%
“…These have been found in all the mammalian species that have been examined to date (9,10). PPAR-␥ is highly expressed in cancer cells, and treatment with PPAR-␥ ligands can induce cell differentiation and apoptosis (11)(12)(13). Existing endogenous ligands for PPAR-␥ include polyunsaturated fatty acids and the eicosanoids 15-deoxy-⌬12,14-prostaglandin J2 (15d-PGJ2), 13-hydroxyoctadecadienoic acid, and 15-hydroxyeicosatetraenoic acid (14,15).…”
mentioning
confidence: 99%
“…And the cellular viability of U251 cells was reduced by 48.26% after incubation with pioglitazone 72 h at 100uM pioglitazone. The dates showed that U87 cells seemed to be more sensitive to pioglitazone than U251 cells, which was not accordant with previous finding showed that U251 cells were more sensitive than U87 cells in their response to pioglitazone [24]. And, U87 cells were used for remaining experiments.…”
Section: Pioglitazone Reduced Cellular Viability and Induced Apoptosimentioning
confidence: 69%
“…PPARg can be activated by synthetic ligands which belonged to the thiazolidinedione (TZD) class, such as pioglitazone, troglitazone, ciglitazone [37,38]. It has been suggested that TZDs have a role of anti-glioma and can suppress the growth of glioma cells in vitro and in vivo glioma models [24,39,40]. In addition, a research conducted by Chen GL prove that pioglitazone can promote alternative splicing of REST pre-mRNA and produce a truncated protein which lose a domain essential for nuclear translocation [15].…”
Section: Discussionmentioning
confidence: 99%
“…In human bladder carcinoma, 15d-PGJ 2 at a dose of 10 µM for 72 h reduced the cell survival by 90% compared with the control group (29). PPARγ agonists have been reported to block migration in several types of cancer cells (15,30). Pioglitazone, a ligand of PPARγ, suppresses human glioma cell proliferation and migration and triggers glioma cell apoptosis (15).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that p120-catenin (p120-ctn) regulates cell motility through the reduction of Rho GTPase activity (14). The PPARγ agonists, pioglitazone and rosiglitazone, inhibit cell growth and invasion via blocking β-catenin (β-ctn) in human glioma cells and colorectal cancer cells, respectively (15,16). The role of adherens junctions in the action of PPARγ agonists in thyroid carcinoma cells remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%